2007
DOI: 10.1161/01.res.0000257913.42552.23
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Play an Essential Role in the Development of Cardiac Hypertrophy

Abstract: Abstract-MicroRNAs are naturally existing, small, noncoding RNA molecules that downregulate posttranscriptional gene expression. Their expression pattern and function in the heart remain unknown. Here we report an array of microRNAs that are differentially and temporally regulated during cardiac hypertrophy. Significantly, the muscle-specific microRNA-1 (miR-1) was singularly downregulated as early as day 1 (0.56Ϯ0.036), persisting through day 7 (0.29Ϯ0.14), after aortic constriction-induced hypertrophy in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
577
2
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 709 publications
(625 citation statements)
references
References 35 publications
39
577
2
6
Order By: Relevance
“…Abdellatif's group found that miR-1 was singularly downregulated as early as day 1, persisting through day 7, after TAC-induced hypertrophy in a mouse model (6). Overexpression of miR-1 carried by adenovirus vector inhibited its in silico-predicted growth-related targets, including Ras guanosine-triphosphatase-activating protein, cyclin-dependent kinase 9, fibronectin, and Ras homolog enriched in brain, in addition to protein synthesis and cell size (Fig.…”
Section: Micrornas and Cardiac Hypertrophy And Heart Failurementioning
confidence: 95%
See 2 more Smart Citations
“…Abdellatif's group found that miR-1 was singularly downregulated as early as day 1, persisting through day 7, after TAC-induced hypertrophy in a mouse model (6). Overexpression of miR-1 carried by adenovirus vector inhibited its in silico-predicted growth-related targets, including Ras guanosine-triphosphatase-activating protein, cyclin-dependent kinase 9, fibronectin, and Ras homolog enriched in brain, in addition to protein synthesis and cell size (Fig.…”
Section: Micrornas and Cardiac Hypertrophy And Heart Failurementioning
confidence: 95%
“…Recently, since 2005, the exciting research on the biological roles of miRNAs in the mammalian cardiovascular system has become a most rapidly evolving field. Several studies have demonstrated the importance of miRNAs not only in cardiovascular development, but also in cardiovascular disease (5)(6)(7)(8). In the present article, the currently relevant findings on the role of miRNAs in cardiac hypertrophy and heart failure will be summarized and the target genes and signaling pathways linking these miRNAs in the context will be discussed.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, the work on miRNAs has been focused especially on hypertrophy, heart failure, and the control of electrical activity in the heart. Several studies have reported that some miRNAs are either increased (e.g., miR-195) [27] or decreased (e.g., miR-1, miR-133) [28] in response to dysregulated ion dynamics during pathological heart conditions. Importantly, alterations in the expression of miRNA may underlie the process producing the dysfunctional cardiac excitability and arrhythmic death [29].…”
Section: Mirnas and Alterations Of Their Expression In Response To MImentioning
confidence: 99%
“…More and more evidences have been shown that miRNAs have critical roles in participating and regulating various cardiovascular diseases, such as cardiac arrhythmia 4, cardiac hypertrophy 5, 6, cardiac injuries 7 and finally the heart failure 8. It has been reported that several miRNAs are involved in the development and progression of cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%